Кραιπάλη: ¿‘Borrachera’ o ‘resaca’?* - Aguilar, Rosa Maria (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2001)
in disagrament with some spanish interpretations of kraipak as drunkeness , this papper aims to show that hangover is the more apropiate reading